Nationwide Monitoring of Antimicrobial-Resistant Escherichia coli and Enterococcus spp. Isolated From Diseased and Healthy Dogs and Cats in Japan - Furuya, Yukari; Matsuda, Mari; Harada, Saki; Kumakawa, Mio; Shirakawa, Takahiro; Uchiyama, Mariko; Akama, Ryoko; Ozawa, Manao; Kawanishi, Michiko; Shimazaki, Yoko; Sekiguchi, Hideto (Frontiers in Veterinary Science, 2022)
The Japanese Veterinary Antimicrobial Resistance Monitoring System (JVARM) was established for nationwide monitoring of antimicrobial-resistant bacteria isolated from animals. Here, antimicrobial resistance of Escherichia coli and Enterococcus spp. isolates from diseased and healthy dogs and cats was investigated. Isolates were collected from diseased dogs and cats and from healthy dogs and cats in 2018 to 2020. Minimum inhibitory concentrations were determined for 1873 E. coli and 1383 Enterococcus spp. isolates. E. coli isolates were most commonly resistant to nalidixic acid [diseased dog (DD), 62.1%; diseased cat (DC), 59.9%; healthy dog (HD), 23.5%; healthy cat (HC, 24.0%] and ampicillin (DD, 54.4%; DC, 64.1%; HD, 28.4%; HC, 25.2%), followed by ciprofloxacin (DD, 45.0%; DC, 44.0%; HD, 12.9%; HC, 10.4%). Enterococcus spp. isolates were most resistant to tetracycline (DD, 66.9%; DC, 67.8%; HD, 47.0%; HC, 52.0%), followed by erythromycin (DD, 43.2%; DC, 46.6%; HD, 27.8%; HC, 34.0%) and ciprofloxacin (DD, 27.9%; DC, 43.7%; HD, 9.7%; HC 12.9%). Only a few E. coli isolates were resistant to colistin and none were resistant to meropenem. Also, none of the Enterococcus spp. isolates we have tested were resistant to vancomycin. The significantly higher resistance rates of E. coli and Enterococcus spp. isolates from diseased, as opposed to healthy, dogs and cats against most of the tested antimicrobials indicates that the use of antimicrobials could select resistant E. coli and Enterococcus spp.